SECURITY FOR COSTS IN THE 1982 PIL ACT: THE RESPONSIBILITY OF THE STATE FOR DISCRIMINATION? - Marjanovic, Sanja; Živković, Mirko (Zbornik radova Pravnog fakulteta u Nišu, 2020)
Although the security for costs (cautio judicatum solvi ) as a procedural institute is not per se in collision with the aliens’ right of access to justice, it could produce equally negative effects. Depending on its conception, cautio judicatum solvi could lead to the breach of the anti-discrimination principle and to the violation of the Serbian Constitution. By imposing the duty of security for costs only to foreign nationals, without taking into consideration any other criterion (except for the reciprocity), Serbian nationals living abroad who have no assets in Serbia are unjustifiably privileged. Moreover, this fact deprives cautio judicatum solvi of its meaning. From the perspective of the defendant winning the case, whose protection is the primary goal of the security for costs, there is a concern about the prospective enforcement of the order for costs if plaintiff does not have property in Serbia. In such circumstances, it is irrelevant whether the plaintiff has a foreign nationality or the Serbian nationality. At the same time, the compatibility of such provision on cautio judicatum solvi with the Constitution could be questioned. It leads to the conclusion that Article 82 of the 1982 PIL Act calls for urgent alteration in order to prevent the discrimination which is currently present.
Keywords: акторска кауција; ЗРСЗ (1982); дискриминација; држављанство; Нацрт новог ЗМПП (2014)